PENGEMBANGAN EKOWISATA MANGROVE BERBASIS KONSERVASI DI PESISIR KABUPATEN KUBU RAYA, KALIMANTAN BARAT - Fitra Wira Hadinata; Dewi Nur Khayani; Hartika Tria; Pa’o Homius Pao; Nabil Zurba (Journal of Aceh Aquatic Sciences, 2020)
The mangrove ecosystem is a community of plants or forests that are able to adapt to salinity and tides. The composition and structure of mangrove vegetation differ both spatially and temporally. The potential for the use of mangrove ecosystems in West Kalimantan is in areas that have been developed as a mangrove ecotourism destination, one of which is the Standing Bay Mangrove which is located on the coast of Kubu Raya Regency. This conservation-based ecotourism can optimize the potential of the mangrove ecosystem by paying attention to ecological sustainability and creating economic value coastal tourism areas. The purpose of this paper is to determine the concept of mangrove ecotourism development based on conservation. However, with the current pandemic situation, research cannot be carried out directly in the field, so what is done is to analyze the conservation-based mangrove ecotourism development strategy from journals related to this paper. Tourism potential that can be developed is carried out, namely analyzing the carrying capacity of the area, developing ecotourism products with special interest in mangroves, increasing the quality of competent resources, the effectiveness of rehabilitation and wise enforcement of mangrove protection regulations, improving infrastructure, community involvement in developing mangrove ecotourism so that the potential for mangrove ecotourism can be utilized optimally. Develop mangrove conservation and rehabilitation activities as one of the leading tourism programs.